Comparison of the Success Rate of Radial Arterial Cannulation with Palpation Techniques and Ultrasound Guidance in Patients Undergoing Major Surgery with General Anesthesia - Afriza Rizqi Zaini; Fredi Heru Irwanto; Mayang Indah Lestari; Erial Bahar; SNA Ratna Sari Devi (HM Publisher, 2022)
Background: Ultrasound-guided arterial cannulation has the potential to increase the total success rate and first attempt and reduce complications compared to conventional landmark palpation methods. This study aims to compare the success rate of radial artery cannula with palpation techniques and ultrasound guidance in patients undergoing major surgery under general anesthesia. Methods: This study is a randomized controlled trial singly. The inclusion criteria for this study were patients who underwent both emergency and elective surgery under general anesthesia, aged >18 years, with ASA I and II physical status. The study sample (60 people) was randomized by computer and divided into two groups (ultrasound guidance and palpation technique). The study will assess the success of the first insertion of the radial artery cannula in both groups. Data analysis was performed with SPSS 25 univariate and bivariate. Results: There is a significant relationship with the success of the first attempt at an ultrasound-guided cannula trial with a p-value of 0.045 with an odds ratio of 3.33 with a 95% confidence interval (0.998 – 11.139). Conclusion: Ultrasound-guided arterial cannulation has a better success rate and fewer complications than conventional palpation techniques.